Comparison between wide‐field digital imaging system and the red reflex test for universal newborn eye screening in Brazil. Issue 7 (24th May 2021) - da Cunha, Laura Pires; Cavalcante Costa, Marcelo Alexandre Agra; de Miranda, Homero Augusto; Reis Guimarães, Juliana; Aihara, Teruo; Ludwig, Cassie A.; Rosenblatt, Tatiana; Callaway, Natalia F.; Pasricha, Malini; Al‐Moujahed, Ahmad; Vail, Daniel; Ji, Marco H.; et al.
Abstract: Purpose: To compare neonatal eye screening using the red reflex test (RRT) versus the wide‐field digital imaging (WFDI) system. Methods: Prospective cohort study. Newborns ( n  = 380, 760 eyes) in the Maternity Ward of Irmandade Santa Casa de Misericórdia de São Paulo hospital from May to July 2014 underwent RRT by a paediatrician and WFDI performed by the authors. Wide‐field digital imaging (WFDI) images were analysed by the authors. Validity of the paediatrician's RRT was assessed by unweighted kappa [κ] statistic, sensitivity, specificity, positive predictive value (PPV) and negative predictive value (NPV). Results: While WFDI showed abnormalities in 130 eyes (17.1%), RRT was only abnormal in 13 eyes (1.7%). Wide‐field digital imaging (WFDI) detected treatable retina pathology that RRT missed including hyphema, CMV retinitis, FEVR and a vitreous haemorrhage. The sensitivity of the paediatrician's RRT to detect abnormalities was poor at 0.77% (95% confidence interval, CI, 0.02%–4.21%) with a PPV of only 7.69% (95% CI, 1.08%–38.85%). Overall, there was no agreement between screening modalities (κ = −0.02, 95% CI, −0.05 to 0.01). The number needed to screen to detect ocular abnormalities using WFDI was 5.9 newborns and to detect treatable abnormalities was 76 newborns. Conclusion: While RRT detects gross abnormalities that preclude visualization of the retina (i.e. media opacities and very large tumours), only WFDI consistently detects subtle treatable retina and optic nerve pathology. With a higher sensitivity than the current gold standard, universal WFDI allows for early detection and management of potentially blinding ophthalmic disease missed by RRT.